Superconducting properties of fullerenes in the mixed state (Review Article) - Buntar, V.; Weber, H.W. (Физика низких температур, 1996)
A review of magnetization measurements and their evaluation in terms of critical fields and characteristic lengths in fullerene superconductors is presented. Typical results of magnetization curves are shown and the evaluation of the superconducting fraction from these measurements is discussed. We also discuss results on determination of the critical fields and characteristic lengths by different experimental techniques and make a comparison of these results between granular and crystalline samples.